Analysis of Determinants of Nurse Compliance in Implementing Standard Precautions to Prevent Healthcare-Associated Infections (HAIs) at Imelda General Hospital for Indonesian Workers - Gultom, Yohania Premita; Nasution, Sri Wahyuni; Ginting, Chrismis Novalinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
People come to hospitals with a hope of recovery, yet unfortunately some go home with a new infection which can vary from mild, moderate, severe, even to sepsis which can be life-threatening. Nosocomial infections or what is currently better known as Health-care Associated Infections (HAIs) refer to infections acquired from the hospital environment, either due to care services or from visitors who visit the hospital. The aims of this research are: Analyzing the factors that influence nurses' compliance in carrying out standard precautions to prevent Healthcare Associated Infections (HAIs) at RSU Imeldakerja Indonesia Medan. This type of research is quantitative research that uses a correlational design. The population in this study is all nursing staff working at the Indonesian Workers' Imelda RSU (RSU IPI) Medan in 2024, totaling 110 people. The data analysis used in this research is univariate, bivariate and multivariate analysis. The results of the research show that from the results of the bivariate analysis the variables of knowledge, information and training, facilities and infrastructure, management support and perceptions of risk influence nurses' compliance in carrying out standard precautions to prevent Healthcare Associated Infections (HAIs) at RSU Imelda Kerja Indonesia (RSU IPI) Medan and only the workload variable has no effect. The results of simultaneous multivariate analysis of the independent variables in this study have an effect on the dependent variable. The factor that most influences nurses' compliance in carrying out standard precautions to prevent Healthcare Associated Infections (HAIs) at RSU Imelda Kerja Indonesia (RSU IPI) Medan is Information and Training.